Perivascular epithelioid cell tumour of the bladder - Tarplin, Sarah (BMJ Publishing Group, 2014)
A 39-year-old woman presented with a long history of pelvic pain and urinary urgency. Prior workup by her primary care doctor had been negative. The patient's gynaecologist ultimately referred her to a urologist following an ultrasound that revealed a possible bladder mass. MRI of the abdomen and pelvis demonstrated a 4 cm soft tissue lesion arising from the bladder. Cystoscopy showed an atypical mass on the anterior bladder wall, and pathological examination of the TURBT (transurethral resection of the bladder tumour) specimen revealed a perivascular epithelioid cell tumour (PEComa) with involvement of the detrusor muscle. The patient underwent a robotically assisted laparoscopic partial cystectomy. Final pathology confirmed a PEComa with negative margins. The patient had an uncomplicated postoperative course and is doing well following surgery. A surveillance cystoscopy at 6 months showed no evidence of recurrence. This case underscores the variability of clinical presentation of PEComas while proposing an appropriate method of surgical management.